Factores de riesgo que influyen en la morbilidad materna, parto, postparto en el Hospital Básico San Miguel, periodo enero – julio 2024. - Bayas Gavilán, Deysi Margoth (2024)
Maternal morbidity constitutes a critical challenge for the health system, manifesting itself in complications during pregnancy, childbirth and postpartum that can put the mother's life at risk. The main objective of this study is to identify the risk factors that influence maternal morbidity during childbirth and postpartum at the San Miguel Basic Hospital in the period between January and July 2024. The methodology used is applied and non-experimental, data will be collected through surveys and direct interviews with participants, complemented by the analysis of existing medical records. The research is descriptive and transversal in nature, to include a specific period of six months. “Socioeconomic, biological, and environmental factors play a significant role in maternal morbidity, identified as contributing factors to low family income, lack of access to adequate prenatal services, and unfavorable environmental conditions. These findings will allow the development of more effective interventions to improve practices and care protocols at the San Miguel Basic Hospital, as well as to formulate more efficient health policies.”. “Identifying specific risk factors is crucial for developing strategies and interventions that aim to reduce maternal morbidity. Its application will have a significant impact on the quality of care and health of women during pregnancy, childbirth and postpartum at the San Miguel Basic Hospital.”